MANTLE PRECONDITIONING BY MELT EXTRACTION DURING FLOW: THEORY AND PETROGENETIC IMPLICATIONS - Pearce Ju.A. (My University, 2005)
Mantle preconditioning may be defined as the extraction of small melt fractions from mantle asthenosphere during its flow to the site of magma generation. Equations may be written for mantle preconditioning, assuming that the mantle comprises enriched ‘plums’ in a depleted matrix. The equations take into account variations in mass fraction of plums, the relative rate of melting of plums and matrix, the temperature and pressure of melt extraction, the mass fraction of melt extracted, the extent of chemical exchange between plums and matrix, and the efficiency of melt extraction. Monitoring mineralogical changes and variations in partition coefficients along the inferred P–T–t path of the mantle asthenosphere allows the equations to be correctly applied to the conditions under which melt extraction takes place. Numerical experiments demonstrate the influence of petrogenetic variables on the shape of melt extraction trajectories and provide new criteria for distinguishing between melt extraction and mixing as the cause of regional geochemical gradients. Representative examples of arc–back-arc systems (Scotia), continental break-up (Afar) and plume–ridge interaction (Azores) indicate that the compositions of the mantle sources of mid-ocean ridge basalts and island arc basalts may be determined, at least in part, by the melt extraction histories of their asthenospheric sources.